PENJUALAN KOSMETIK TOKO KAWAII BEAUTY DENGAN FITUR REQUEST BERBASIS WEBSITE - Yulianti, Eka; Khristianto, Teguh (Information Technology and Telematics, 2018)
Abstract - Kawaii Beauty Shop is an online store that sells various beauty products to support your daily appearance. The purpose of this study was to create a website-based cosmetic sales information system. The method used to build the system development is the waterfall method. System design using UML and system implementation using PHP and MySQL. The results of the research on the Kawaii Beauty Store can be concluded that the construction of a cosmetics sales website can help broader product marketing. And makes it easy for buyers to make order transactions, purchase products as desired and get information about the Kawaii Beauty Shop.